(untitled) (Research Nepal Journal of Development Studies, 2019)
Human trafficking arise from Labor Migration, Poverty, Exclusion, Attractions of Cities, Open Boarder, Active Trafficker, Bad Governance and solutions for the problems are Inland Job Opportunity, Poverty Alleviation Programs, Inclusion and Participation, Rural Education, Secured Boarder, Active Social Worker and Good Governance are urgently needed in Nepal. To identify the problem and solutions of human trafficking from Nepal the study has been conducted. In-depth interview method had been applied and had interviewed with security personnel of the Sunauli boarder of both countries. Prevention, Care, Monitoring and Evaluation from both countries are also necessary. Entire issues of problem and solutions of human trafficking in between India and Nepal are virgin area of research.